2015
DOI: 10.22146/ijc.21207
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fluorescence Carbon Nanoparticles from Ascorbic Acid

Abstract: Carbon nanoparticles (C-dot) ABSTRAK Nanopartikel karbon (C-dot) merupakan material yang termasuk ke dalam kelas nanopartikel 0 dimensi yang bersifat fotoluminesen. C-dot dapat disintesis dari berbagai sumber asam-asam organik melalui metode

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
2
12
1
1
Order By: Relevance
“…It was also found that the higher the amounts of urea in the synthesis of C-dots, the higher the agglomeration of formed C-dots. However, similar to that reported by Sugiarti [10], emission intensity increased with the increased concentration of urea as a passivation agent in the reaction process. The photoluminescence from C-dots that have surface passivation is attributed to the presence of surface energy traps that become emissive upon stabilization [13].…”
Section: Catalyst Preparation Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It was also found that the higher the amounts of urea in the synthesis of C-dots, the higher the agglomeration of formed C-dots. However, similar to that reported by Sugiarti [10], emission intensity increased with the increased concentration of urea as a passivation agent in the reaction process. The photoluminescence from C-dots that have surface passivation is attributed to the presence of surface energy traps that become emissive upon stabilization [13].…”
Section: Catalyst Preparation Resultssupporting
confidence: 88%
“…The maximum fluorescence emission of C-dot was at the wavelength of 536.33 nm when it was excited at a wavelength of 405 nm ± 10. The recorded maximum emission spectrum was higher than reported by Sugiarti [10], where C-dot synthesized from ascorbic acid-urea 75% has a maximum emission at wavelength 500 nm when excited at a wavelength of 400 nm. This difference may be due to the influence of passivation agent concentration on C-dots in the reaction process.…”
Section: Spectrum Of Fluorescence Intensitycontrasting
confidence: 65%
See 1 more Smart Citation
“…The characteristics of C-dots are not like nanodiamonds (Ding et al, 2014), C-dots are materials that belong to the class of 0dimensional nanoparticles that are photoluminescence (Sugiarti & Darmawan, 2015). C-dots below 10 nm have a framework of sp 2 hybridized carbon atoms, abundant oxygen residues (Fang et al, 2012) and the surface is coated with groups of oxygen, polymers, or other species (Bao et al, 2015;Smagulova et al, 2017;Strauss et al, 2014;Unnikrishnan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…C-dots are nanoparticles that emit light or fluoresce, are not toxic compared to similar alternatives such as quantum dots [2]. C-dots are materials belonging to the class of 0-dimensional nanoparticles that have photoluminescence (PL) properties [4] with a size below 10 nm, having an sp 2 hybridized carbon atom structure with abundant oxygen residues [5] and their surfaces coated with oxygen groups, polymer, or other species [6,7].…”
Section: Introductionmentioning
confidence: 99%